Estudo do processo de biossorção do corante Preto Reativo 5 utilizando a macrófita Limnobium spongia - Suzaki, Pedro Yahico Ramos (2013)
This work aimed to study the removal of dye Reactive Black 5 using as biosorbent macrophyte Limnobium spongia. It was investigated the influence of milling the biomass, the particle size, the chemical pretreatment adsorbent with the solution of NaOH 0.1 mol L¬-1 and H2SO4 0.1 mol L-1 , the stirring speed and also the influence of temperature and pH parameters. It was also determined adsorption kinetics and equilibrium. In the study of the influence of grinding, it was observed that the biomass of ground Limnobium spongia showed better results in the adsorption of the dye than the entire biomass. The different particle sizes and pretreatment of biomass tested did not influence significantly the removal of the dye. In the study stirring rate was observed that from 100 rpm external diffusional resistances are reduced to a minimum. The parameters pH and temperature were studied jointly by the method Central Composite Rotatable Design (CCRD), behavior demonstrated that these parameters are independent and greater amount of dye removed occurred at the maximum temperature 49.8°C and at pH 0.8. The kinetic study was made at temperatures of 20 and 50° C, the maximum amount of dye removed and the equilibrium time was of 81.97 mg g-1 and 6 h to 20°C and 105.6 mg g-1 and 4 h to 50°C. The kinetic data were best represented by pseudo-second order model. The equilibrium isotherms were performed at temperatures of 20, 30, 40 and 50º C. The highest removal of dye was 108.17 mg g-1 at 50°C and amount removed was 86 mg g-1 at 20°C. The equilibrium data of isotherms at all temperatures were predicted by the Langmuir model.